Ocean predation and mortality of adult Atlantic salmon - Strøm, John Fredrik; Rikardsen, Audun H.; Campana, Steven E.; Righton, David; Carr, Jonathan; Aarestrup, Kim; Stokesbury, Michael J.W.; Gargan, Patrick G.; Caballero Javierre, Pablo; Thorstad, Eva Bonsak (Scientific Reports, 2019)
Published version, licensed CC BY-NC-ND 4.0. , available at: https://doi.org/10.1038/s41598-019-44041-5 Predation and mortality are often difficult to estimate in the ocean, which hampers the management and conservation of marine fishes. We used data from pop-up satellite archival tags to investigate the ocean predation and mortality of adult Atlantic salmon (Salmo salar) released from 12 rivers flowing into the North Atlantic Ocean. Data from 156 tagged fish revealed 22 definite predation events (14%) and 38 undetermined mortalities (24%). Endothermic fish were the most common predators (n = 13), with most of these predation events occurring in the Gulf of St. Lawrence and from the Bay of Biscay to the Irish Shelf. Predation by marine mammals, most likely large deep-diving toothed whales (n = 5), and large ectothermic fish (n = 4) were less frequent. Both the estimated predation rates (ZP) and total mortality rates (ZM) where higher for Atlantic salmon from Canada, Ireland, and Spain (ZP = 0.60– 1.32 y−1, ZM = 1.73–3.08 y−1) than from Denmark and Norway (ZP = 0–0.13 y−1, ZM = 0.19–1.03 y−1). This geographical variation in ocean mortality correlates with ongoing population declines, which are more profound for southern populations, indicating that low ocean survival of adults may act as an additional stressor to already vulnerable populations.